Chronometric investigations of the Middle to Upper Paleolithic transition in the Zagros Mountains using AMS radiocarbon dating and Bayesian age modelling. Issue 109 (August 2017) - Becerra-Valdivia, Lorena; Douka, Katerina; Comeskey, Daniel; Bazgir, Behrouz; Conard, Nicholas J.; Marean, Curtis W.; Ollé, Andreu; Otte, Marcel; Tumung, Laxmi; Zeidi, Mohsen; Higham, Thomas F.G.
Abstract: The Middle to Upper Paleolithic transition is often linked with a bio-cultural shift involving the dispersal of modern humans outside of Africa, the concomitant replacement of Neanderthals across Eurasia, and the emergence of new technological traditions. The Zagros Mountains region assumes importance in discussions concerning this period as its geographic location is central to all pertinent hominin migration areas, pointing to both east and west. As such, establishing a reliable chronology in the Zagros Mountains is crucial to our understanding of these biological and cultural developments. Political circumstance, coupled with the poor preservation of organic material, has meant that a clear chronological definition of the Middle to Upper Paleolithic transition for the Zagros Mountains region has not yet been achieved. To improve this situation, we have obtained new archaeological samples for AMS radiocarbon dating from three sites: Kobeh Cave, Kaldar Cave, and Ghār-e Boof (Iran). In addition, we have statistically modelled previously published radiocarbon determinations for Yafteh Cave (Iran) and Shanidar Cave (Iraqi Kurdistan), to improve their chronological resolution and enable us to compare the results with the new dataset. Bayesian modelling results suggest that the onset of the Upper Paleolithic in the Zagros Mountains dates to 45, 000–40, 250 cal BP (68.2% probability). Further chronometric data are required to improve the precision of this age range.